Parametric Optimization Of Magneto-Rheological Fluid Damper Using Particle Swarm Optimization - Mohd Azraai, M. Razman; Priyandoko, Gigih; A. R., Yusoff; M. F. F., Ab Rashid (Universiti Malaysia Pahang, 2015)
This paper presents a parametric modeling of a magneto-rheological (MR) damper using a Particle Swarm Optimization (PSO) method. The objective of this paper is to optimize the parameter values of the MR fluid damper behavior using the Bouc-Wen model. The parametric identification was imposed beforehand in replicating the behavior of the MR fluid damper. The algebraic function from a number of hysteresis models was steered by comparing selected models: Bingham, Bouc-Wen and BoucWen by Kwok. A simulation method was operated in investigating these models by employing MATLAB reliant from the model intricacy. The experimental data was presented in terms of the time histories of the displacement, the velocity and the force parameters, measured for both constant and variable current settings and at a selected frequency applied to the damper. The model parameters were determined using a set of experimental measurements corresponding to different current constant values. It has been shown that the MR damper model’s response via the proposed approach is in good agreement with the MR damper test rig counterpart